A broad-spectrum antibiotic adjuvant SLAP-S25: one stone many birds - Meirong Song; Kui Zhu (Microbial Cell)
The rapid emergence of antibiotic resistance has caused serious threat to global health. The worldwide search for novel classes of antibiotics to combat multidrug-resistant (MDR) bacteria is barren since about half a century ago. One of the promising strategies to combat the MDR pathogens is the combinational therapy. For instance, trimethoprim and clavulanic acid are routinely used to enhance the efficacies of sulfonamides and β-lactam antibiotics in clinic, respectively. Nevertheless, such adjuvants are specific for certain classes of antibiotics. We hypothesized that the combinational treatments with antibiotic adjuvants targeting the bacterial membrane may potentiate other antibiotics against MDR Gram-negative pathogens. In our recent publication (Song et al., doi: 10.1038/s41564-020-0723-z), we demonstrate a short linear antibacterial peptide SLAP-S25, which potentiates multiple antibiotics with different modes of action against Gram-negative bacteria. The mechanism studies show that SLAP-S25 targets both lipopolysaccharide (LPS) in the outer membrane and phosphatidylglycerol (PG) in the inner membrane of Escherichia coli. The impaired bacterial membrane caused by SLAP-S25 promotes the intracellular accumulation of antibiotics in bacteria. Our results indicate that the bacterial membranes are promising targets for the discovery of new antibiotics or antibiotic adjuvants to combat MDR bacteria associated infections.